Adeno-associated virus (AAV) cell entry: structural insights. Issue 5 (May 2022) - Meyer, Nancy L.; Chapman, Michael S.
Abstract : Adeno-associated virus (AAV) is the leading vector in emerging treatments of inherited diseases. Higher transduction efficiencies and cellular specificity are required for broader clinical application, motivating investigations of virus–host molecular interactions during cell entry. High-throughput methods are identifying host proteins more comprehensively, with subsequent molecular studies revealing unanticipated complexity and serotype specificity. Cryogenic electron microscopy (cryo-EM) provides a path towards structural details of these sometimes heterogeneous virus–host complexes, and is poised to illuminate more fully the steps in entry. Here presented, is progress in understanding the distinct steps of glycan attachment, and receptor-mediated entry/trafficking. Comparison with structures of antibody complexes provides new insights on immune neutralization with implications for the design of improved gene therapy vectors. Highlights: High-resolution cryogenic electron microscopy (cryo-EM) structures detail adeno-associated virus (AAV) receptor protein binding interactions. AAV's glycan 'primary receptors' are recharacterized as 'attachment factors'. AAV5-like viruses interact with a different domain of the receptor using a binding site that is distinct from that of other AAVs. The epitopes of many AAV-neutralizing antibodies overlap with receptor-binding sites on the capsid. Future structural focus will be on AAV receptor-independent pathways and additional steps in entry and trafficking.